Revisiting the Role of Peaceful Means of Dispute Settlement in the Preah Vihear Temple Dispute - Thuy, Bui Thu (VNU Journal of Science: Legal Studies; Vol 42 No 2, 2026)
The border and sovereignty dispute surrounding the Preah Vihear Temple (“Preah Vihear Dispute”) between Cambodia and Thailand is one of the most prolonged and complex conflicts in Southeast Asia. To resolve the dispute, Cambodia and Thailand have employed peaceful measures ranging from negotiation and mediation to judicial means. Among these, the International Court of Justice (ICJ) has examined the case twice, first in 1962 and again in 2013. However, the issue of the border demarcation around the Preah Vihear Temple remains unresolved. As a result, tensions in the area have remained until now. On May 28, 2025, military forces from Cambodia and Thailand clashed at the border area between Preah Vihear Province (Cambodia) and Ubon Ratchathani Province (Thailand), resulting in the death of a Cambodian soldier. The border dispute between the two nations has once again escalated. Both governments have expressed their intention to resolve the dispute peacefully on the basis of international law. However, the complex internal political dynamics of each country are making these efforts increasingly difficult. This article will provide an overview of the Preah Vihear Dispute; reiterate the obligation of States to resolve disputes through peaceful means in accordance with international law; analyze and assess the successes and limitations of applying these measures to the Preah Vihear case; and offer a forecast on the viability of peaceful measures in resolving the conflict between Cambodia and Thailand. Keywords:  .